Resepsi Fungsional Surah Al-Fātiḥaḥ di Kalangan Disabilitas Sensorik Rungu Wicara Rumah Qur’an Sahabat Tuli Asy-Syukur Kediri - Fajrianti, Faricha Cahya; Mukaromah, Kholila (Canonia Religia, 2024)
This article aims to understand more deeply how surah Al-Fātiḥaḥ is perceived and functioned practically by people with hearing and speech sensory disabilities (PDSRW) at the Qur'an House of the Deaf Friends Asy-Syukur Kediri. In the Islamic tradition, surah Al-Fātiḥaḥ is believed to have great spiritual power, so it is not surprising that this surah is perceived and used in various ways by various groups. The functional reception of the Qur'an is then used to analyze the purpose of reciting surah Al-Fātiḥaḥ at RQST Asy-Syukur. This study is a field research using a qualitative approach. Data collection was done through observation, interview, and documentation. The results obtained show that the practice of reciting al-Fātiḥaḥ at RQST Asy-Syukur Kediri is carried out regularly before and after learning. The recitation of surah al-Fātiḥaḥ in this practice is used as a source of help and guidance so that students can understand and appreciate the learning process, especially in the study of the meaning of the Qur'an. Given that each santri has a different intensity of hearing and intellectual ability, this also affects their speed in capturing information. So the recitation of surah al-Fātiḥaḥ is intended to make it easier for students to understand the material presented. On the other hand, Maskurun, the caregiver of the Qur'an House, perceives surah al-Fātiḥaḥ to make it easier for him to deliver the material. In addition, surah al-Fātiḥaḥ is used as a daily practice of the santri and functions as a wirid or prayer. This research is expected to add to the richness of the living Qur'an treasure in a new dimension, namely how the Qur'anic text lives and is practiced among people with disabilities, a topic that is relatively rarely raised in Islamic studies.